2022
DOI: 10.1088/1681-7575/ac5ef9
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic effects in a gas modulated Invar-based dual Fabry–Pérot cavity refractometer

Abstract: By measuring the refractivity and the temperature of a gas, its pressure can be assessed from fundamental principles. The highest performing instruments are based on Fabry-Perot cavities (FPC). Gas modulation refractometry (GAMOR)is a methodology that has the ability to reduce the influence of disturbances to such an extent that high-precision (sub-parts-per-million) assessments of pressure can be made by the use of FPCs of Invar. To allow for high accuracy assessments, it is of importance to assess the uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Here, gas temperatures vary due to thermodynamic pV-work when the gas is introduced into the refractometer. Recent simulations revealed a designdependent heating of the gas by more than 50 K followed by a decay with sub-second time constants [27]. The QCLAS technique presented could be used to experimentally validate these simulations due to its excellent time resolution and non-invasive character.…”
Section: Discussionmentioning
confidence: 91%
“…Here, gas temperatures vary due to thermodynamic pV-work when the gas is introduced into the refractometer. Recent simulations revealed a designdependent heating of the gas by more than 50 K followed by a decay with sub-second time constants [27]. The QCLAS technique presented could be used to experimentally validate these simulations due to its excellent time resolution and non-invasive character.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, since Invar has a three times larger volumetric heat capacity than glass (in fact, it has a more than three orders of magnitude larger volumetric heat capacity than the gas), it was concluded that the initial heating of the cavity walls will be at least two orders of magnitude smaller than that of the FLOC system. It was then also found that the increased gas temperature decays exponentially towards the cavity wall temperature with a time constant of 0.14 s and that it is within 1 mK of the temperature of the wall already after 1.5 s [7].…”
Section: Introductionmentioning
confidence: 92%
“…The gas thereafter rapidly adopts the temperature of the cavity walls. For the case with 30 kPa of N2, it was found that the decay is exponential with a time constant of 0.07 s, while, for 100 kPa, it is 0.14 s. This implies that the average temperature of the centre part of the cavity will quickly (within 1 -2 s) equalize to temperatures well within sub-mK of that of the cavity wall [7].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations